CREATIVE THINKING STUDENT ACTIVITIES IN SOLVING PROBLEMS IN PROBABILITY MATERIALS IN GRADE VII SMP PGRI 08 MALANG - Anton Prayitno; Nia Wahyu Damayanti; Regina Rede Niga (JMPM: Jurnal Matematika dan Pendidikan Matematika, 2021)
This research was conducted to answer the questions that have been formulated, namely to find out the activities of students thinking creatively conducted class VII SMP PGRI 08 Malang in solving problems in the topic of probability The purpose of this research is to find out the creative thinking done by students. One method that will be used by researchers to find out students' creative thinking in solving math problems is by giving tests. This researcher aims to describe the student's job description or specific circumstances. Data collection was done by the method of test and interview. The researchers found that students were able to work on problems in three components: fluency, flexibility, and novelty. This research is describing the activities of students thinking creatively of junior high school students in solving mathematical problems. The research subjects consisted of SMP PGRI 08 Malang, which was one of the students who could think creatively, which was an instrument, a matter of tests capable of mathematics by working on a topic of  probability.